(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2024)
Tourism attractiveness is the basis for the functioning of tourism. Due to its subjective nature, it is a phenomenon that is difficult to analyze. The aim of the article is to indicate the importance of attractiveness in choosing a tourist destination. The article is a literature review. Reference was made to both domestic and foreign literature. The functions and forms of tourism, the concept and essence of tourist attractiveness and its impact on the choice of a tourist destination are discussed. This influence is direct and decisive. The broadly understood tourism attractiveness has its share in every stage of choosing a tourist destination – from the choice of the direction of travel, through the choice of route, accommodation, meals, to the choice of additional attractions accompanying the trip.